Coal burning-derived SO2 and traffic-derived NO2 are associated with persistent cough and current wheezing symptoms among schoolchildren in Ulaanbaatar, Mongolia - Dambajamts Enkh-Undraa; Seiji Kanda; Masayuki Shima; Takaki Shimono; Mari Miyake; Yoshiko Yoda; Saijaa Nagnii; Toshimasa Nishiyama (Komiyama Printing Co. Ltd, 2019)
Abstract Background Children in Ulaanbaatar are exposed to air pollution, but few epidemiological studies have been conducted on the effects of environmental risk factors on children's health. Also, no studies have yet examined the prevalence of respiratory symptoms in children in suburban areas, where air quality-monitoring stations have not yet been installed. This cross-sectional study evaluated the associations between outdoor air pollution and respiratory symptoms among schoolchildren in urban and suburban districts of Ulaanbaatar. Methods The ATS-DLD-78 C questionnaire was used to investigate the respiratory symptoms of schoolchildren aged 6-12 years (n = 1190) who lived in one of three urban districts or a suburban district of Ulaanbaatar. In each district, the outdoor concentrations of nitrogen dioxide (NO2) and sulfur dioxide (SO2) were measured at two sites (at ≤100 m and > 100 m from the nearest major road) in the 2-year period from 2015 to 2016. The associations between health outcomes and exposure to air pollutants were estimated using the multinomial logistic regression method. Results The outdoor concentration of SO2 was significantly associated with persistent cough symptom (OR = 1.12, 95% CI 1.04-1.22). Furthermore, the outdoor concentration of NO2 was significantly associated with the current wheezing symptom (OR = 1.33, 95% CI 1.01-1.75) among children in urban and suburban. Conclusions The prevalence of persistent cough symptom was markedly high among the schoolchildren in urban/suburban districts of Ulaanbaatar. Overall, the increases in the prevalence of respiratory symptoms among children might be associated with ambient air pollution in Ulaanbaatar.